2021
DOI: 10.1002/jbm4.10536
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐Size Distribution and Frequency‐Dependent Attenuation in Human Cortical Tibia Bone Discriminate Fragility Fractures in Postmenopausal Women With Low Bone Mineral Density

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Specifically, we have found that the presence of large pores is detrimental to image quality. Such large pores are characteristic of degraded bone and were associated with weak femoral strength ex vivo [35] and with fracture risk [41]. This may appear to be a major obstacle to bone imaging for some individuals with a high risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we have found that the presence of large pores is detrimental to image quality. Such large pores are characteristic of degraded bone and were associated with weak femoral strength ex vivo [35] and with fracture risk [41]. This may appear to be a major obstacle to bone imaging for some individuals with a high risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Following Armbrecht et al [17], the fragility fracture discrimination performance of BDAT and DXA was assessed by means of multivariate Partial Least Square discrimination analyses with Leave-One-Out Cross-Validation (PLS-LOOCV) using the libPLS library [44]. Significant parameters were used to build a first set of discrimination models used to predict vertebral, non-vertebral, and all fragility fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cortical bone appears as a homogenized material, which elasticity can be parametrized with porosity [56]. Recently, it has been shown that cortical thinning and accumulation of large cortical pores in the tibia reflect local structural deterioration of the femoral neck and can predict fragility fractures [10,17]. The second HR-pQCT generation, with a lower resolution, is able to resolve the larger pores, usually associated with resorption cavities [17].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Transducer characteristics, such as transducer aperture, may also affect the successful transmission of ultrasound through the bone and alter the amount of information available in the resulting pressure field. 35 Alternate methods for determining tissue properties in vivo, such as novel ultrasonic cortical backscatter methods or other quantitative ultrasound techniques for determining attenuation coefficients 38,39 and speed of sound in bone 40 may help supplement or compare with the strategies outlined in this work.…”
Section: Limitationsmentioning
confidence: 99%